2014
DOI: 10.1056/nejmoa1401177
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Outcomes for Severe Combined Immunodeficiency, 2000–2009

Abstract: BACKGROUND The Primary Immune Deficiency Treatment Consortium was formed to analyze the results of hematopoietic-cell transplantation in children with severe combined immunodeficiency (SCID) and other primary immunodeficiencies. Factors associated with a good transplantation outcome need to be identified in order to design safer and more effective curative therapy, particularly for children with SCID diagnosed at birth. METHODS We collected data retrospectively from 240 infants with SCID who had received tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
609
3
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 653 publications
(652 citation statements)
references
References 37 publications
22
609
3
18
Order By: Relevance
“…B-SCID genotypes, active infection at time of HCT, and graft-versus-host disease (GVHD) are all associated with poor T cell recovery 3,7,8,17 . Evaluation of T cell reconstitution should include enumeration of T cell populations (i.e., CD3, CD4 and CD8 T cell counts), naïve (CD4+CD45RA+) T cells and/or recent thymic emigrants (CD4+/CD45RA+/CD31+), and T cell function via proliferation to mitogens and/or anti-CD3.…”
Section: Immune Reconstitutionmentioning
confidence: 99%
See 3 more Smart Citations
“…B-SCID genotypes, active infection at time of HCT, and graft-versus-host disease (GVHD) are all associated with poor T cell recovery 3,7,8,17 . Evaluation of T cell reconstitution should include enumeration of T cell populations (i.e., CD3, CD4 and CD8 T cell counts), naïve (CD4+CD45RA+) T cells and/or recent thymic emigrants (CD4+/CD45RA+/CD31+), and T cell function via proliferation to mitogens and/or anti-CD3.…”
Section: Immune Reconstitutionmentioning
confidence: 99%
“…There are few large studies reporting on late effects following transplantation for SCID 7,11,13,33 . Prospective studies are needed to investigate long-term survival and quality of life, immune reconstitution, need for stem cell boost or second transplantation, and rates of GVHD by SCID genotype and phenotype, donor source, graft manipulation, and conditioning regimen.…”
Section: Research Priorities and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For many patients with PID, partial donor chimaerism is sufficient to induce cure if the affected recipient cell lineage is replaced completely or partially by donor cells, although complete donor chimaerism is best in some diseases (Gennery 2015). Pai et al (2014) reported the results of 240 infants who received a transplant for SCID, at 25 centres in the USA between January 2000 and December 2009. The overall survival rate at 5 years was 74%; most deaths were within the first year after transplant and were due to infections (39%) or pulmonary complications (37%).…”
Section: Non-scid Primary Immunodeficienciesmentioning
confidence: 99%